2003
DOI: 10.1109/mm.2003.1240213
|View full text |Cite
|
Sign up to set email alerts
|

Energy-efficient network memory for ubiquitous devices

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 26 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…The overall energy drained by the transmission layer, is hence given by the sum of fixed and variable energy consumptions of all its network interfaces, subject to the current network load. Some reference values about the transmission-related power consumption of mobile terminals, have been presented in [52], [54], [55], [56] for cellular, Wi-Fi and Bluetooth technologies. An excerpt of these data, is reported, for the sake of completeness, in Table IV.…”
Section: B Transmission-layer Energy Consumptionmentioning
confidence: 99%
“…The overall energy drained by the transmission layer, is hence given by the sum of fixed and variable energy consumptions of all its network interfaces, subject to the current network load. Some reference values about the transmission-related power consumption of mobile terminals, have been presented in [52], [54], [55], [56] for cellular, Wi-Fi and Bluetooth technologies. An excerpt of these data, is reported, for the sake of completeness, in Table IV.…”
Section: B Transmission-layer Energy Consumptionmentioning
confidence: 99%
“…Table I contains power consumption numbers that we use as parameters in our power savings estimate. These parameters are primarily compiled from a number of publications including research papers [9], [16], [17], DRAM device vendors' data sheets [18], [19], [20] and low-power system design guides [4]. In our estimate of power saving benefits, we do not consider power consumption reduction in FSB, IO interconnect and LCD panel backlight when the display is in idle modes.…”
Section: B Quantitative Evaluationmentioning
confidence: 99%
“…Data on energy dissipation in some of the commercial processors and network links are reported by Fryman et al [11] and similar information but at the level of instruction execution can be found in some of the documents related to Instruction Level Power Analysis [24]. Although our intuition is based on the conventional wisdom "compute more and communicate less", very recently this wisdom has been challenged by some researchers, mostly arguing in the line that architectural features in modern processors hinder the power savings expected from the reduction in communication [11,4]. For example, Barr and Asanovic [4] show that compressing files before releasing it onto the wireless, may end up increasing the energy needs, due to various factors such as the DRAM to cache ratio, cache miss rates and so on.…”
Section: Related Workmentioning
confidence: 99%